Interacting with Foreign Industrial Clusters - A Case Study of Swedish Companies in Japanese Clusters - Asplund,August; Walde,Oscar (2021)
Clusters, agglomerations of companies in related industries, are a phenomenon which have been widely accepted to increase the productivity of its constituent companies. Many scholars hold the view that companies should utilise these favourable conditions and interact with clusters. Nevertheless, there exists limited literature on the topic how companies can interact with clusters outside of their home base. Thus, the purpose of the study is to identify and explore what methods companies can utilise to interact with clusters outside of their home base and why they choose a certain strategy, by focusing on what interaction strategies Swedish companies have utilised to interact with Japanese clusters. This is addressed through a case study with seven Swedish companies that interacts with Japanese clusters. The study finds that there are two categories of interaction modes, co-location modes and re-mote modes. Co-location modes include establishing a subsidiary, joint venture, and integrated or independent acquisition. Remote modes include distributors, technology scouting and inter-cluster networking. An additional mode is interaction through an accelerator or an incubator which can be both a co-location mode and a remote mode. Unlike previous entry mode catego-risations, the taxonomy presented here is specifically suited for cluster interaction and includes non-transactional modes. Furthermore, the interaction strategy, which is a combination of the interaction mode and the activities allocated to the cluster, is found to be affected by the three factors: the motives for cluster interaction, the company’s characteristics and the cluster’s characteristics. The study shows that Swedish companies most commonly establish a subsidiary to interact with Japanese clusters, but that there are also examples of integrated acquisitions and remote interaction modes. Most companies have sales and supporting functions but there are also cases with R&D and production allocated to the cluster.
Keywords: Industry Cluster; Cluster Strategy; Interaction Strategy; Tap into; Sweden; Japan; Internationalisation